2015
DOI: 10.4314/ajtcam.v12i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content distribution and antioxidant activities of <i>Terminalia sericea</i> Burch

Abstract: Background: Terminalia sericea has been used traditionally for the treatment of diseases associated with oxidative stress. This study was aimed at determining the distribution of phenols in the leaves, stem bark and root bark of Terminalia sericea and their antioxidant activity. Materials and methods: Hot and cold water, methanol/acetone extracts were evaluated for their total phenolic content (TPC), flavone/flavonol content (FFC), flavonone/dihydroflavone content (FDFC), hydroxycinnamic acid derivative conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This study also demonstrated that the stem contained more antioxidant compounds compared to the fruit, leaves, and root. In a previous study [ 39 ], the crude extracts of T. sericea stem displayed higher antioxidant activity compared to the leaves and the root. The ester bound extractable phenolics displayed the highest average antioxidant activity compared to the free, glycoside bound extractable phenolics and non-extractable (insoluble) phenolics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also demonstrated that the stem contained more antioxidant compounds compared to the fruit, leaves, and root. In a previous study [ 39 ], the crude extracts of T. sericea stem displayed higher antioxidant activity compared to the leaves and the root. The ester bound extractable phenolics displayed the highest average antioxidant activity compared to the free, glycoside bound extractable phenolics and non-extractable (insoluble) phenolics.…”
Section: Resultsmentioning
confidence: 99%
“…The crude extract of the root has been reported to be toxic to Monkey kidneys or Vero cells [ 36 ]. Previous studies [ 37 , 38 , 39 ] on the antioxidant activities of T. sericea have been limited to extractable antioxidants. Lupeol, inseparable mixtures of epicatechin-catechin and epigallocatechin-gallocatechin have been identified as antioxidant constituents of the acetone extract of stem bark [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH free radical scavenging ability of the crude extract and fractions F 1 , F 2 , F 3 , F 4 and F 5 was determined according to the spectrophotometric method of Anokwuru et al [ 29 ]. A 125 mM DPPH/methanol solution was prepared by dissolving 10 mg DPPH in 200 mL methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The reducing power was determined according to the method of Anokwuru et al [ 29 ]. A 0.2 M (pH 6.6) sodium phosphate buffer (50 µL) and 50 µL of the crude extract, fractions F 1 , F 2 , F 3 , F 4 and F 5 , and compound 4 were added in triplicate in the first three wells of a 96-well plate, followed by serial dilution.…”
Section: Methodsmentioning
confidence: 99%
“…This result agreed with some reports in the literatures. Anokwuru, et al [17] reported higher yields of Acalypha wilkesiana, Azadirachta indica and Solanum scabrum in methanol extraction than in acetone. Also, Dhawan and Gupta [18] observed the highest extract yields in methanol solvent for all the plants studied.…”
Section: Dry Extract Yieldmentioning
confidence: 99%